LOW-DEGREE MELTING OF A METASOMATIZED LITHOSPHERIC MANTLE FOR THE ORIGIN OF CENOZOIC YULONG MONZOGRANITE-PORPHYRY, EAST TIBET: GEOCHEMICAL AND SR-ND-PB-HF ISOTOPIC CONSTRAINTS - Jiang Y.H.; Jiang S.Y.; Ling H.F.; Dai B.Z. (My University, 2006)
SHRIMP zircon U-Pb dating, mineral chemical, element geochemical and Sr-Nd-Pb-Hf isotopic data have been determined for the Yulong monzogranite-porphyry in the eastern Tibet, China. The Yulong porphyry was emplaced into Triassic strata at about 39 Ma. The rocks are weakly peraluminous and show shoshonitic affinity, i.e., alkalis-rich, high K2O contents with high K2O/ Na2O ratios, enrichment in LREE and LILE. They also show some affinities with the adakite, e.g., high SiO2 and Al2O3, and low MgO contents, depleted in Y and Yb, and enrichment in Sr with high Sr/Y and La/Yb ratios, and no Eu anomalies. The Yulong porphyry has radiogenic 87Sr/86Sr (0.7063-0.7070) and unradiogenic 143Nd/144Nd (εNd = -2.0 to -3.0) ratios. The Pb isotopic compositions of feldspar phenocrysts separated from the Yulong porphyry show a narrow range of 206Pb/204Pb ratios (18.71-18.82) and unusually radiogenic 207Pb/204Pb (15.65-15.67) and 208Pb204Pb (38.87-39.00) ratios. In situ Hf isotopic composition of zircons that have been SHRIMP U-Pb dated is characterized by clearly positive initial εHf values, ranging from +3.1 to +5.9, most between +4 and +5. Phenocryst clinopyroxene geothermometry of the Yulong porphyry indicates that the primary magmas had anomalously high temperature (>1200 °C). The source depth for the Yulong porphyry is at least 100 km inferred by the metasomatic volatile phase (phlogopite-carbonate) relations. Detailed geochemical and Sr-Nd-Pb-Hf isotopic compositions not only rule out fractional crystallization or assimilation-fractional crystallization processes, but also deny the possibility of partial melting of subducted oceanic crust or basaltic lower crust. Instead, low degree (1-5%) partial melting of a metasomatized lithosphere (phlogopite-garnet clinopyroxenite) is compatible with the data. This example gives a case study that granite can be derived directly by partial melting of an enriched lithospheric mantle, which is important to understand the source and origin of diverse granites. © 2005 Elsevier B.V. All rights reserved.
Keywords: EAST TIBET; GEOCHEMISTRY; GRANITE; METASOMATIZED LITHOSPHERIC MANTLE; SR-ND-PB-HF ISOTOPES; Мезозой::Триасовая; Mesozoic::Triassic